Educators’ Perspectives on Cybersecurity: Case of Resource-Constrained Schools in South Africa - (:unkn) unknown (My University, 2024)
Cybersecurity has become a global security priority in recent years. Many African countries have embarked on important efforts to improve their cybersecurity posture in all sectors, including education. The increased use of information communication technologies by educators implies a greater exposure to cyber threats and risks prompting the need for cybersecurity to become a priority for schools. Cyber threats and risks have the potential to disrupt school operations and compromise the safety of learners, educators, administration staff, parents, and the surrounding community. The way respective stakeholders engage with cybersecurity and respond to cybersecurity intervention will, to an extent, depend on their perspective of the phenomena. There is paucity on literature on African educators’ perspectives on cybersecurity as a starting point. This study aims at answering the question: What are perspectives on cybersecurity of educators in resource-constrained schools in South Africa? The study used a qualitative exploratory case study methodology. Data was collected through in-depth and semi-structured interviews from four schools in the Western Cape and Limpopo provinces; these represent an affluent and a rural province. It was analysed using thematic analysis based on the Social Cognitive Theory. Findings suggest that when it comes to cybersecurity, educators’ self-efficacy is low, and their outcome expectancy is negative. Their socio-structural environment does not provide enough support to boost their confidence due to their exposure to ICTs, cybersecurity awareness, and available resources. The more a school is resource-constrained, the less educators prioritise cybersecurity. The study contributes to cybersecurity in education by shedding light on the cybersecurity perspectives of educators in resource-constrained schools in South Africa to pave the way for initiatives that cultivate a culture of cyber safety.
Keywords: African Research